Discrepancies among Scopus, Web of Science, and PubMed coverage of funding information in medical journal articles - Kokol, Peter; Blažun Vošner, Helena (Journal of the Medical Library Association, 2018)
Objective: The overall aim of the present study was to compare the coverage of existing research funding information for articles indexed in Scopus, Web of Science, and PubMed databases.Methods: The numbers of articles with funding information published in 2015 were identified in the three selected databases and compared using bibliometric analysis of a sample of twenty-eight prestigious medical journals.Results: Frequency analysis of the number of articles with funding information showed statistically significant differences between Scopus, Web of Science, and PubMed databases. The largest proportion of articles with funding information was found in Web of Science (29.0%), followed by PubMed (14.6%) and Scopus (7.7%).Conclusion: The results show that coverage of funding information differs significantly among Scopus, Web of Science, and PubMed databases in a sample of the same medical journals. Moreover, we found that, currently, funding data in PubMed is more difficult to obtain and analyze compared with that in the other two databases. This article has been approved for the Medical Library Association’s Independent Reading Program.